2007
DOI: 10.1152/ajpheart.00663.2006
|View full text |Cite
|
Sign up to set email alerts
|

Immunogold labeling study of the distribution of GLUT-1 and GLUT-4 in cardiac tissue following stimulation by insulin or ischemia

Abstract: Whereas glucose transporter 1 (GLUT-1) is thought to be responsible for basal glucose uptake in cardiac myocytes, little is known about its relative distribution between the different plasma membranes and cell types in the heart. GLUT-4 translocates to the myocyte surface to increase glucose uptake in response to a number of stimuli. The mechanisms underlying ischemia-and insulin-mediated GLUT-4 translocation are known to be different, raising the possibility that the intracellular destinations of GLUT-4 follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 42 publications
1
30
0
Order By: Relevance
“…14 The rationale for Glut-1 staining was based on previous studies using endothelial expression of Glut-1 as a marker of active de novo capillary formation; where 75% of Glut-1 expression in the heart was localized to the capillary endothelium. 23 The morphological assessment of its expression was used as a surrogate marker of relaxin's pro-angiogenic properties, and to supplement the a-SMA staining of larger vessels. In this study, we were able to demonstrate that relaxin's anti-fibrotic, anti-apoptotic and pro-angiogenic actions acted in synergy during post-infarct healing without overt adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 The rationale for Glut-1 staining was based on previous studies using endothelial expression of Glut-1 as a marker of active de novo capillary formation; where 75% of Glut-1 expression in the heart was localized to the capillary endothelium. 23 The morphological assessment of its expression was used as a surrogate marker of relaxin's pro-angiogenic properties, and to supplement the a-SMA staining of larger vessels. In this study, we were able to demonstrate that relaxin's anti-fibrotic, anti-apoptotic and pro-angiogenic actions acted in synergy during post-infarct healing without overt adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Serial sections were also used for immunohistochemical staining and morphometric analysis of various selected markers associated with collagen turnover, utilizing monoclonal antibodies to a-smooth muscle actin (a-SMA; a marker for myofibroblast differentiation; 1:250 dilution; Dako) and MMP-13 (collagenase-3; 1:100 dilution, Calbiochem) in addition to a polyclonal antibody to TGF-b1 (1:200 dilution, Santa-Cruz Biotechnology). Macrophage infiltration (inflammation) was assessed utilizing a monoclonal antibody to f4/80 (a transmembrane protein present on the cell surface of mouse macrophages; 1:50 dilution; Serotec); angiogenesis was detected by a-SMA (smooth muscle) and glucose transporter (Glut-1; endothelial 23 ) staining of vessels using a polyclonal antibody to Glut-1 (1:1000 dilution; Chemicon International); while cardiomyocyte apoptosis was detected using the ApopTag (TUNEL based) Plus Peroxidase assay kit (Millipore). Detection of antibody staining was completed using various DAB-based kits: the Vectastain ABC kit for a-SMA, f4/80 and Glut-1, the Dako ARK (mouse on mouse) kit for MMP-13 and the Dako EnVision anti-rabbit kit for TGF-b1.…”
Section: Histology and Morphometric Analysismentioning
confidence: 99%
“…Heart muscle glucose transport shares many similarities to that occurring in skeletal muscle and is known to be associated with the translocation of the GLUT4 glucose transporter isoform from intracellular reservoir compartments to the limiting membranes of the sarcolemma and the transverse-tubule system of the cardiomyocytes (Fischer et al, 1997). Using immunogold labelling of GLUT4 in heart cells, Slot et al reported insulin stimulation of GLUT4 translocation to both sarcolemma and the transverse-tubules membranes (Slot et al, 1997), whereas Davey et al reported some selectivity in translocation to the transverse-tubules (Davey et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…GLUT1 is expressed in cardiomyocytes (13,14,51) and endothelial cells (9). GLUT1 is generally considered to be primarily involved in basal heart glucose transport but also undergoes translocation to plasma membranes in response to insulin (14,51).…”
Section: Stimulation Of Glut Translocation By Insulin: Quantificationmentioning
confidence: 99%
“…GLUT1 is also expressed in the heart, both in cardiac myocytes, where it has a role in basal glucose uptake (14,41,51), and in endothelial cells (9). GLUT1 undergoes modest translocation to the sarcolemma with insulin and ischemia (14,51), as it does in adipocytes (50).…”
mentioning
confidence: 99%